Self-perception and perception of leadership behaviours of Special Olympics Portugal coaches - Pedro Pires; Marco Batista; Helena Mesquita; Sergio J. Ibáñez (Federación Extremeña de Balonmano; University of Extremadura, 2022)
Coaches have a fundamental role in the holistic development of their athletes, and when we talk about adapted sports, this prerogative gains more relevance, since sports are a transforming vehicle in the athletes' lives. However, the theme of the leadership behaviors of coaches of athletes with intellectual disabilities is little scientifically explored. The main purpose of this study is to identify the coaches' self-perception and the athletes' perception about the leadership behaviors of the Special Olympics Portugal coaches. It is also intended to examine the relationship between self-perception and perception with the formal training of coaches. The research is descriptive and cross-sectional, with a sample consisting of 50 coaches and 94 athletes from the universe of Special Olympics Portugal. The sport leadership scale was the instrument used in the study, in the self-perception and perception versions. The results showed that, in the versions analysed, the coaches of athletes with intellectual disabilities showed more leadership behaviours in the dimensions of reinforcement, training, instruction and social support. The coaches with specific training in the area of disability have more appropriate behaviours to the specific characteristics and needs of the athletes.